Electrochemical studies of poly (3,4-ethylenedioxythiophene) PEDOT/VS2 nanocomposite as a cathode material for rechargeable lithium batteries - Murugan, A. Vadivel; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Electrochemistry Communications, 2005)
Here, we demonstrate the electrochemical characterization of a new type of layered poly (3,4-ethylenedioxythiophene) PEDOT/ VS2 nanocomposite. It has been prepared via flocculation of delaminated VS2 with subsequent in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. The interlayer spacing Of VS2 expands from 5.71 to 14.01 A and this interlayer separation is consistent with the existence of a monolayer of PEDOT in the VS2 framework. X-ray diffraction, XPS and TEM studies have been;shown the change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT/VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mAh/g) compared to that (80 mAh/g) for pristine VS2. (C) 2004 Published by Elsevier B.V.
Keywords: layered nanocomposite; lithium batteries; polythiophene; vanadium disulfide

Enhancement of double-layer capacitance behavior and its electrical conductivity in layered poly (3, 4-ethylenedioxythiophene)-based nanocomposites - Murugan, A. Vadivel; Viswanath, A. K.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Applied Physics Letters, 2005)
In this letter, we report on the enhanced double-layer capacitance of a layered poly (3, 4-ethylene dioxythiophene) PEDOT-MoO3 nanocomposite, which has been synthesized by a novel microwave irradiation method. The x-ray photoelectron spectroscopy analysis shows the changes in electron density and the shift in binding energy suggesting charge transfer from sulfur atoms upon PEDOT intercalation between MoO3 layers. The room-temperature conductivity for the PEDOT-MoO3 composite is found to be 1.82x10(-1) S cm(-1), which is four orders of magnitude higher than that of the pristine oxide (3.78x10(-5) S cm(-1)). The enhanced double-layer capacitance of the PEDOT-MoO3 nanocomposite (similar to 300 F g(-1)) compared to that (similar to 40 mF g(-1)) of pristine MoO3 is attributed to higher electronic conductivity, enhanced bidimensionality, and increase in surface area of the nanocomposite.

Entrapment of poly(3,4-ethylenedioxythiophene) between VS2 layers to form a new organic-inorganic intercalative nanocomposite - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Vijayamohanan, K. (Journal of Materials Chemistry, 2005)
Here we report the synthesis and characterization of a new class of nanocomposite by direct in situ oxidative polymerization of 3,4-ethylenedioxythiophene (EDOT) with VS2 as a host material in the presence of an external oxidizing agent. Upon intercalation, the interlayer spacing of VS2 expands from 5.71 Angstrom to 14.01 Angstrom, followed by exfoliation and a restacking process facilitating expansion of the lattice in a direction perpendicular to the dichalcogenide layers. This change in interlayer separation is consistent with the existence of two phases of organic and inorganic species in the nanocomposites corresponding to the intercalation of PEDOT in the VS2 framework. The resulting nanocomposite is characterized by thermal analysis (TGA), X-ray diffraction, FTIR, SEM, TEM, and four-probe electrical conductivity measurements. The application potential of the nanocomposite as a cathode material for rechargeable lithium batteries is also demonstrated by the electrochemical intercalation of lithium into the PEDOT-VS2 nanocomposite, where a significant enhancement in the discharge capacity is observed (similar to130 mA h g(-1)) compared to that (80 mA h g(-1)) for pristine VS2.

Eu3+ doped lanthanum oxide nanowhiskers: microwave hydrothermal synthesis, characterization and photoluminescence properties - Murugan, A. Vadivel; Viswanath, Annamraju Kasi; Kakade, Bhalchandra A.; Ravi, V.; Saaminathan, V. (Journal of Physics D-Applied Physics, 2006)
We report here a straightforward and rapid microwave - hydrothermal route providing an easy synthesis of Eu3+ doped La2O3 nanowhiskers. The nanostructured Eu3+ doped La2O3 is characterized by x-ray diffraction studies, scanning electron microscopy and photoluminescence (PL). The emission spectrum shows transitions from the excited 5D(0) state to F-7(J) (J = 0, 1, 2, 3, 4) levels of the Eu3+ ion. The most intense peak around 611 nm is due to the D-5(0) -> F-7(2) transition, expected from the Judd-Ofelt selection rules. PL spectra measurements demonstrate that the lanthanum oxide nanowhisker shows higher PL intensity.

Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons